Chagas disease: prevalence of Trypanosoma cruzi infection in patients of a general hospital: Chagas in a general hospital (Actualizaciones en Sida e Infectología, 2024)
Chagas disease affects more than 7 million people worldwide, the majority in Latin America. In Argentina it is estimated that there are 2 million infected. Objectives: Determine the prevalence of Trypanosoma cruzi infection in patients treated in an adult infectious disease service and characterize said population. Population: patients followed with a diagnosis of Trypanosoma cruzi infection, made by serology, considering infection in those with at least 2 of 3 positive techniques (HAI/ELISA/IFI) from the same sample. Data were obtained retrospectively from 90 medical records. Results: The prevalence of infection was 3%, of which 50% were Argentine. 85.5% were women in the age range between 31-45 years. The educational level was low. The diagnosis was made in the context of pregnancy in 53%. Chronic Chagas clinical presentation without obvious pathology predominated (62%). 94.5% with treatment criteria, 39% received it. Conclusions: The prevalence is similar to that published by other authors. Argentine nationality predominated in women of childbearing age diagnosed in the context of pregnancy. A large percentage was in the clinical phase without target organ injury, something predictable given the epidemiological characteristics of the group. Almost all of them were eligible for treatment, although less than half received it. This may be due to the difficulty in following up after diagnosis. We emphasize the importance of raising patients' awareness about adhering to the consultation with the possibility of cure with timely treatment.
Keywords: Chagas’s disease. Trypanosoma cruzi infection.